A discrete convolution involving Fourier sine and cosine series and its applications. Issue 3 (3rd March 2020) - Thao, Nguyen Xuan; Tuan, Vu Kim; Dai, Nguyen Anh
ABSTRACT: In this paper, we introduce a discrete convolution involving both the Fourier sine and cosine series. We study Young's type inequality and a discrete transform related to this convolution and solve in closed form a class of discrete Toeplitz plus Hankel equations.